Sudden Deaths: Taking Stock of Political Connections - Parsley, David C.; Faccio, Mara (Journal of Financial and Quantitative Analysis, 2009)
Many firms voluntarily incur the costs of attempting to influence politicians. However, estimates of the value of political connections have been made in only a few cases. We propose a new approach to valuing political ties that builds on these previous studies. We consider connected to a politician all companies headquartered in the politician’s home town, and use an event study approach to value these ties at their unexpected termination. Analysis of a large number of sudden deaths from around the world since 1973 reveals a market adjusted 1.7% decline in the value of connected companies. Our results suggest connections matter in many countries, and that they are more important for family firms, firms with high growth prospects, firms operating in industries over which the politician has jurisdiction, and firms headquartered in highly corrupt countries. † Both authors are from the Owen Graduate School of Management, Vanderbilt University. We thank the Financial Markets Research Center for financial support, two anonymous referees, Nick Bollen, Ettore Croci, Ray Fisman, Tim Loughran, Paul Malatesta, Maria Teresa Marchica, Tobias Moskowitz (the Editor), Roberto Mura, Joe Peek, Raghu Rau, Jorg Rocholl, Antoinette Schoar, Paul Schultz, Jordan Siegel, Bernard Yeung, and seminar participants at City University (London), Erasmus University (Rotterdam), International Monetary Fund, London School of Economics, Southern Methodist University, Tilburg University, University of Amsterdam, University of Illinois, Vanderbilt University, and at the 2005 HKUST Finance Symposium for insightful comments and suggestions. We thank Zhengfeng Guo for assistance in collecting data on the hometown of the successors of the deceased politicians. Mara Faccio also acknowledges financial support from the Hirtle Callaghan Research Scholar Award.